, 15.01.2020keananashville

# Which of the following is the sum of the polynomials 5x2 - 4x + 1 and -3x2 + x - 3 ? 2x2 + 3x + 2 8x2 - 5x - 2 2x2 - 3x - 2 -8x2 - 3x - 2

A. 2x2 - 3x - 8

Just subtract the functions and combine like terms
(f - g)(x) = f(x) - g(x)
(f - g)(x) = 2x^2 - 5 -(3x + 3)
(f - g)(x) = 2x^2 - 5 - 3x - 3
(f - g)(x) = 2x^2 - 3x - 8

option 4

Step-by-step explanation:

Given the x- intercepts say x = a, x = b, x - c then the corresponding factors are

(x - a), (x - b), (x - c) and the polynomial is the product of the factors

Here the x- intercepts are x = 3, x = 0, x = - 1, thus the factors are

(x - 3), (x - 0), (x - (- 1) , that is

(x - 3), x and (x + 1) , then

y = ax(x - 3)(x + 1) ← where a is a multiplier

To find a substitute (1, - 8) into the equation

- 8 = a(1 - 3)(1 + 1) = - 4a ( divide both sides by - 4 )

a = 2, thus

y = 2x(x - 3)(x + 1) ← expand factors using FOIL

= 2x(x² - 2x - 3) ← distribute by 2x

= 2x³ - 4x² - 6x

B. 3x4 + x3 - 2x2 + 3x + 2

Step-by-step explanation:

3x4 - 2x3 + 4x - 2 + 3x3 - 2x2 - x + 4 add the like terms (the ones with same power)

3x4 (there's no other term with 4th power so we leave this one as it is)

-2x3 + 3x3 = x3

-2x2 (this one as well will be as it is)

4x - x = 3x

-2 + 4 = 2

a

Step-by-step explanation:

Step-by-step explanation:

The axis of symmetry is the line that is smack dab in the middle of the shape. The only way you can do this is if you graph all 4 equations, and see which one has an axis of symmetry of 1.5. The picture below is showing all of the equations and their graphs color-coded. The black dotted line is the axis of symmetry a.k.a. x=1.5

As you can see, the axis of symmetry goes perfectly through only equation A, making A the answer.

-2/3

Step-by-step explanation:

4+3x=2

3x=2-4

3x=-2

X= - 2/3

-2/3 or - 0.667

Step-by-step explanation:

2 x 2 + 3x = 2

4 + 3x = 2

collect like terms so that components involving x can stand alone

3x = 2 - 4

3x = -2

divide both sides by the coefficient of x which is 3

3x/3 = -2/3

x = -2/3 or -0.667

3x^4 +x^3 -2x^2 +3x +2

Step-by-step explanation:

(3x^4 - 2x^3 + 4x -2) + (3x^3 - 2x^2 - x +4)

There are no like terms for 3x^4, so leave it alone.

-2x^3 + 3x^3 = 1x^3

No like terms for -2x^2

4x - x = 3x

-2 + 4 = 2

Answer? 3x^4 +x^3 -2x^2 +3x +2

23838383838383838383838262947293
Just align the polynomials and combine like terms.

### Other questions on the subject: Mathematics

Step-by-step explanation:"Tamara runs 5 miles each week"Let Tamara runs 'x' weeks then equation that represents the total distance covered by Tamara will be,1). y = 5x2). Here 'y'...Read More
Mathematics, 21.06.2019, sakinahunt
3x+12Cross Multiplication 3 and X and 3 and 4 3x + 12...Read More
Mathematics, 21.06.2019, clay373
Step-by-step explanation:Short answer No They are not congruent. The scale factor would be 1 if they were. JL and RT should both be the same length (they are opposite angles marked...Read More